BIOPRODUKSI SENYAWA KIMIA ANTIDIABETES OLEH ISOLAT KAPANG ENDOFIT KUMIS KUCING (Orthosiphon spicatus B. B. S.) - Sulastri, Lilik; Kartika, Rudi; Simanjuntak, Partomuan (PROSIDING SEMINAR KIMIA, 2024)
Kumis kucing plant (Orthosiphon spicatus B. B. S.) are one of the plants that have been used as diuretic, antidiabetic and antihypertensive drugs. Identification of chemical compounds, and antidiabetic activity assay of bioproduction of endophytic fungi with code B.Os.1F that isolated from the stems of kumis kucing have been carried out. Two fermentation methods (dynamic and static fermentation) to determine the pH. The tlc profile analysis and pH showed that B.Os.1F isolate by dynamic fermentation for 12 days had the potential to produce chemical compounds as antidiabetics at pH 4 ~ 6. The product of fermentation are extracted with ethyl acetate, then fractionated by column chromatography (SiO2): (i) n-hexane-ethyl acetate [10:1 ~ 1:1]; (ii) chloroform-methanol (20:1 ~ 1:1) based on “bioassay guided fractionation” with a-glucosidase enzyme inhibition assay. The isolate of B.Os.1F.2-3 had an activity of 76 %, and identify based on UV-Vis, Fourier-Transform Infra Red (FT-IR) spectroscopies and gas chromatography-mass spectrometer (GC-MS) are estimated to be Ergosta-5,7,9(11),22-tetraen-3-ol compounds. Keywords : Endophytic fungus, Orthosiphon spicatus B.B.S., α-glucosidase enzyme, ergosta-5,7,9(11),22-tetraen-3-ol.